THE INFLUENCE OF LEADERSHIP STYLE ON EMPLOYEE PERFORMANCE AT PT. BANK MANDIRI (PERSERO) TBK MAKASSAR AREA - zaenal; Abd. Rahman Kadir; Fauziah Umar (Scientia Integritas Utama, 2023)
This study aims to (1) determine whether the democratic, consultative, delegative and participative leadership styles have a positive and significant effect on employee performancePT. Bank Mandiri (Persero) Makassar Area, (2) Among the four leadership styles mentioned above, which leadership style has the most influence on the performance of PT. Bank Mandiri (Persero) Makassar Area. This research was surveyed at PT. Bank Mandiri (Persero) Tbk Makassar Area. The sample selection used the Stratified Ramdom Sampling method. The variables studied were (1) Employee Performance, (2) Democratic Leadership Style, (3) Consultative, (4) Delegative, and (5) Participatory. Then the data obtained is calculated usingSPSS (Statistical Package for Social Science) computer program package. The results of the study show that (1) simultaneously democratic, delegative, consultative and participatory leadership styles have a positive and significant impact on employee performance at PT. Bank Mandiri (Persero) Tbk Makassar Area. (2) partially, democratic leadership style makes the biggest contribution to improving employee performance at PT. Bank Mandiri (Persero) Tbk Makassar Area. Therefore, leadership with a democratic leadership style is preferred by employees at PT. Bank Mandiri (Persero) Tbk Makassar Area